Hubungan Tingkat Pengetahuan Keputihan dengan Perilaku Hygiene Genitalia Pada Wanita Usia Produktif - Dwi Widyaningrum; Gatut Hardianto; Lilik Djuari (Universitas Malahayati Lampung, 2024)
ABSTRACT Vaginal discharge is a common complaint among women of childbearing age, reproductive age, and puberty. It can occur at all ages, including the productive age. Of all the diseases experienced by women worldwide, 33% are reproductive health problems caused by a lack of knowledge about vaginal discharge. This research is an analytical observational study with a cross-sectional approach. The sample was obtained using purposive sampling, and data from 78 productive-age female respondents. Research instrument using a questionnaire. The statistical test used was Spearman's Rank correlation test. The study shows that 33 individuals (42%) have good knowledge about vaginal discharge, while 41 respondents (53%) have sufficient genital hygiene behavior. The statistical test result with α=0.01 obtained a significance value of p=0.000 and a correlation coefficient value of 0.494. The value of p α indicates a significant relationship between the level of knowledge about vaginal discharge and genital hygiene behavior with a moderate correlation. The statistical test results with α=0.05 indicate a significant relationship (p0.001) with a correlation coefficient of α =0.494 means that there is a significant relationship between the level of knowledge about vaginal discharge and genital hygiene behavior with a moderate correlation. Keywords: Vaginal Discharge, Genital Hygiene, Knowledge, Behavior, Productive Age Women ABSTRAK Keputihan merupakan keluhan umum dikalangan wanita usia subur, usia reproduksi, dan pubertas. Keputihan dapat terjadi pada semua usia termasuk usia produktif. Dari semua penyakit yang dialami wanita di dunia, 33% adalah masalah kesehatan reproduksi yang diakibatkan oleh minimnya pengetahuan tentang keputihan. Penelitian ini bersifat analitik observasional dengan pendekatan cross sectional. Teknik pengambilan sampel dengan purposive sampling didapatkan data 78 responden wanita usia produktif. Instrument penelitian menggunakan kuisioner. Uji statistik yang digunakan adalah uji Spearman's Rank. penelitian menunjukkan 33 responden(42%) memiliki pengetahuan yang baik tentang keputihan, sedangkan 41 responden (53%) memiliki perilaku hygiene genitalia yang cukup. Hasil uji statistik dengan α=0,05 diperoleh nilai signifikansi p0,001 nilai koefisien korelasi (0,494) terdapat hubungan yang bermakna antara tingkat pengetahuan tentang keputihan dengan perilaku hygiene genitalia dengan korelasi sedang. Kata Kunci : Keputihan, Hygiene Genitalia, Pengetahuan, Perilaku, Wanita Usia Produktif